2021
DOI: 10.1002/adfm.202102618
|View full text |Cite
|
Sign up to set email alerts
|

Dual‐Zone Photothermal Evaporator for Antisalt Accumulation and Highly Efficient Solar Steam Generation

Abstract: Interfacial solar steam generation offers a promising and cost‐effective way for saline water desalination. However, salt accumulation and deposition on photothermal materials during saline and brine evaporation is detrimental to the stability and sustainability of solar evaporation. Although several antisalt strategies are developed, it is difficult to simultaneously achieve high evaporation rates (>2.0 kg m−2 h−1) and energy efficiencies. In this study, a self‐rotating photothermal evaporator with dual evapo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
153
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(161 citation statements)
references
References 79 publications
1
153
0
Order By: Relevance
“…An ideal solar steam generation system should be capable of efficient solar energy absorption and high solar-thermal conversion efficiency; it must also possess excellent thermal management performance, efficient water transfer capability, superior salt resistance, long-term stability, and scalable production [10][11][12][13][14]. Researchers have proposed the following several approaches to optimize the different functional components of solar steam generation evaporators.…”
Section: Introductionmentioning
confidence: 99%
“…An ideal solar steam generation system should be capable of efficient solar energy absorption and high solar-thermal conversion efficiency; it must also possess excellent thermal management performance, efficient water transfer capability, superior salt resistance, long-term stability, and scalable production [10][11][12][13][14]. Researchers have proposed the following several approaches to optimize the different functional components of solar steam generation evaporators.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, with less heat loss, the evaporation rate of hydrophobic association hydrogel is higher than that of C-CAHs (Figure 8o). More recently, Wu et al 163 reported a multi-layer spherical evaporator composed of a PS core and multi-layer outer coatings (PS-cellulose-PDA-PPy-PDA). This design reduces its density and restricts water transport only through the outer hydrophilic layers.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…8o). More recently, Wu et al 163 reported a multi-layer spherical evaporator composed of a PS core and multi-layer outer coatings (PS–cellulose–PDA–PPy–PDA). This design reduces its density and restricts water transport only through the outer hydrophilic layers.…”
Section: Solar–thermal Conversion Enhancementmentioning
confidence: 99%
See 1 more Smart Citation
“…[38,39] Meanwhile, the sidewall without light irradiation also undergoes a cold evaporation process, thus the temperature of the sidewall is lower than the ambient temperature, and energy can be collected from the environment. [40,41] The advantage of the 3D structure is that the Solar steam generation (SSG) has attracted increasing interest due to its huge potential in seawater desalination. However, SSG performance is not yet satisfactory due to limited photothermal efficiency and crude thermal management.…”
mentioning
confidence: 99%